Consumer reaction on tumbling funds: Evidence from retail fund outflows during the financial crisis 2007/2008 - Schmidt, Daniel; Schmielewski, Frank (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2025)
Contrary to the findings reported in some of the extant literature, our study indicates that over the past few years a change in investors’ behavior patterns means that investment decisions are made at short notice, and that shares are redeemed in a discriminatory manner when funds perform poorly. By using a data assembled from 1672 retail funds in Germany over the period March 2008 to April 2010, we are able to show that in general, both the prior fund performance and prior net redemptions have a statistically significant influence on fund outflows. Moreover, there are indications that in recent crises situations that have resulted in the withdrawal of shares investors react fast to market signals. Our findings will also highlight areas in which policy-makers, regulatory authorities and the fund industry should establish a strong regulatory framework to prevent liquidity shortages of retail funds.
Keywords: Liquidity Risk; Financial Fragility; Fund Performance; 330 Wirtschaft